Why so slow? The School-to-Work Transition in Italy - Francesco Pastore (Global Labor Organization (GLO), 2017)
This essay provides a comprehensive interpretative framework to understand the reasons why the school-to-work transition (SWT) is so slow and hard in Italy. The country is a typical example of the South European SWT regime, where the educational system is typically rigid and sequential, the labor market has been recently made more flexible through two-tier labor market reforms, and the family has typicallyan important role to absorb the individual and social cost of the passage to adulthood. The main thesis of this essay is that the traditional disorganization of the educational and training system coupled with slow economic growth, rather than the supposedly low degree of labor market flexibility explain high (youth) unemployment. Important reforms of several tiles of the Italian SWT regime – the Jobs Act, important fiscal incentives to hiring youth long term unemployed, the so-called Good School and the related introduction of work-related learning, the European Youth Guarantee and the reform of employment services – have been all recently implemented, which are causing a slow convergence towards the so-called European social model, but it is still too early to draw conclusions as to the impact of such reforms on youth labor market outcomes.
Keywords: H52; I2; I24; J13; J24; 330; School-to-Work Transition; Youth Experience Gap; Human Capital Theory; Dual Principle; European Youth Guarantee; Italy